Violence as a Sign of Complicity (Criminal and Legal Aspect) - Khramtsov, O. M. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article deals with the problems of criminal legal qualification of violent actions of some accomplices of a crime in relation to others with the purpose of involving the latter to a joint commission of the crime. The norm that determines the actions of the perpetrator (co-executor), instigator and accomplice in committing a crime has been analyzes. A suggestion for the improvement of the legislation on criminal liability in this area has been given.